TEACHING A FOREIGN LANGUAGE USING INTERACTIVE TEACHING METHODS IN INSTITUTIONS EDUCATION OF THE I-II LEVEL OF ACCREDITATION - Stepanchuk, N.O.; Ahaponenko, M.O. (Pedagogy of Higher and Secondary Education, 2008)
In article to be considered effectiveness of using interactive methods of studying in the process of learnin foreign languages in higher educational of 1-11 degrees of accreditation.